Teachers’ Perceptions and Experiences of Integrating AI-Based Tools in Classroom Practices in Indonesia - Hendrik Pratama; Laila Fitriana (CV. FoundAE, 2025)
The increasing presence of artificial intelligence (AI) in education raises important questions about preservice teachers’ readiness to integrate AI into future instructional practice. This study examined the extent to which attitudes toward AI predict readiness for AI integration. A quantitative, cross-sectional survey design was used with 212 preservice teachers from an Indonesian university. Data were collected using a validated 22-item Attitudes Toward AI in Education Scale measuring perceived usefulness, ethical and privacy concerns, pedagogical confidence, and professional identity. Descriptive statistics, confirmatory factor analysis, and multiple regression were conducted. Results showed that all four attitudinal dimensions significantly predicted AI readiness, with perceived usefulness emerging as the strongest positive predictor and ethical concerns demonstrating a negative association. These findings highlight the multidimensional nature of AI readiness and underscore the importance of addressing both competence and ethical awareness in teacher preparation. The study contributes empirical evidence to support AI literacy development in teacher education.